Hierarchy precoder design for multi-cell multiuser multiple-input–multiple-output wireless networks with interference alignment - Li, Shidang; Li, Fei; Li, Chunguo; Huang, Yongming; Zhu, Weiping; Yang, Luxi (IET signal processing, 2016)
A hierarchy precoding approach is proposed in this study for multi-cell multiuser systems with any number of base stations and that of users, which is suitable for any number of data streams. The key feature of this approach is aligning the inter-user interferences within the same cell to the room spanned by the inter-cell interferences, by which both the inter-cell and inter-user interferences are cancelled simultaneously. Then, the inter-stream interference for each user can be easily tackled. It is found that the interference alignment-based hierarchy precoder achieves to the full freedom of degree. With interference-free transmissions achieved by the proposed precoder, the transmit power is optimised in an analytical expression by maximising the sum rate and minimising the sum weighted mean square error. Extensive simulations demonstrate the effectiveness of the proposed method.